Internet Financial Reporting: Studi Komparasi Bank Umum Syariah Di Indonesia Dan Malaysia - Taqiyah Dinda Insani; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this study was to determine the differences of Internet Financial Reporting Quality. This study was using quantitative approach with independent sample t test and mann whitney u test. The population of this study was official website of islamic banks in Indonesia and Malaysia. determination of the number of samples using (sampling jenuh), where all of the population is used as a sampel. Data that being used was secondary data. The data was collected from official website of the sentral banks in each country. The result of this study showed that there was significant differences of Internet Fianncial Reporting Quality between Indonesia and Malaysia. The difference is caused there are significant differences between the quality of content and timeliness components. Meanwhile, there is no differences between technology and user support components.